Association Between Hypertensive Disorder in Pregnancy and Postpartum Depression: Hypertensive Disorder in Pregnancy - Nafeesa, .; Gul, Fouzia; Mehsud, Raazia; Bibi, Fatima; Mahmood, Nadia; Hussain, Nazish (Pakistan Journal of Health Sciences, 2025)
Gestational hypertension, preeclampsia, and eclampsia are suspected of spontaneously developing and being particularly critical for maternal and infant health. New research indicates that these disorders may also elevate the probability of developing Postpartum Depression (PPD), which remains one of the serious mental health challenges in new mothers. Objective: To evaluate the prevalence of PPD in women with hypertensive disorders during pregnancy and to examine further the association of PPD with hypertensive disorders of pregnancy. Methods: This comparative cross-sectional study was conducted at the Obstetrics and Gynaecology Department, LMH, Kohat. A total of 155 postnatal women between the ages of 15 and 40 between 2-6 weeks postpartum were included. PPD was evaluated using the Urdu translation of Edinburgh Postnatal Depression Scale (EPDS), with depression indicated by scores >10. SPSS version 25 for statistical analysis, Chi-square tests (p < 0.05) were performed. Results: Women suffering from hypertensive disorders showed significantly higher EPDS scores (mean value of 11.85 ± 3.00) in comparison to those of normotensive women (mean value of 8.71 ± 2.03, p = 0.001). Emotional neglect (p = 0.001) and previous depression (p = 0.001) as risk factors were significantly related to PPD. Hypertensive pregnancies were also linked to adverse neonatal outcomes, including lower birth weights (p = 0.001) and increased neonatal admissions (p = 0.001). Conclusions: Hypertensive disorders in pregnancy significantly increase the risk of PPD. Integrating mental health support into prenatal and postnatal care for hypertensive women may improve maternal psychological well-being and neonatal health outcomes.